Drug disposition and pharmacokinetics with a consideration of pharmacological and clinical relationships - Curry, Stephen H. (London, 1977)
Contents of this book include: Chemical introduction; Disposition and fate; Binding to plasma proteins; Drug concentration in blood and blood fraction,...